VD_FINDINFO AP / 2010 / 188 vom 2. April 2009 - VD Tribunal cantonal (2009)
INTERDICTION DE L'ARBITRAIRE, APPRÉCIATION DES PREUVES, MOYEN DE DROIT CANTONAL, DÉPENS, PRINCIPE D'ALLÉGATION | 4 al. 1 CPC, 444 al. 1 CPC, 444 al. 2 CPC, 444 CPC, 92 al. 1 CPC, 92 al. 2 CPC, 92 al. 3 CPC, 92 CPC, 94 al. 1 CPC, 94 al. 3 CPC, 94 al. 4 CPC, 94 CPC, 9 Cst.